Internationalization of Business Operations- A Strategic Approach - Kaur, Simranjit (Journal of Commerce and Trade, 2013)
The level of participation of firms in international process can be specified by different types of foreign market entry modes. Import and export entry modes are the traditional form of international activities of firms. International licensing and franchising are the example of contractual entry modes. Firms can also undergo international operations by investment entry modes. These involve joint ventures, consisting of contractual operations, equity joint-venture and strategic alliance, and sole ventures or the establishment of a wholly owned subsidiary. As the business environment has increased in uncertainty and complexity, firms must immediately identify the significant changes and respond to them rapidly to continue to exist in the industry. It is generally accepted that the first and the most important motive of the businesses in the capitalism economy is the profit maximization by either increasing the revenue or decreasing the cost of production. In the face of a globally escalating competition, firms not only compete with the rivals in home countries but also the international competitors. Therefore, the pursuit of global profit becomes the key motive of the enterprises. The purpose of this paper is to examine some descriptive frameworks and motivations and the major modes of entering foreign markets to explain the course of internationalization of the firms.